Efek Kombinasi Ekstrak Etanol Daun Anting-Anting (Staphylococcus aureus ) dan Kulit Jeruk Manis (Citrus sinensis) terhadap Bakteri Staphylococcus aureus ATCC 25923 dengan Metode Pita Kertas - Ghani Nurfiana Fadma Sari; Isnaini Nurendra Hidayati; Ana Indrayati; Destik Wulandari; Ismi Puspitasari (Fakultas Farmasi Universitas Setia Budi, 2026)
Infections caused by Staphylococcus aureus ATCC 25923 continue to increase due to antibiotic resistance, making natural product-based antibacterials a promising alternative. This study aimed to evaluate the antibacterial activity and combination effect of ethanol extracts of anting-anting leaves (Staphylococcus aureus) and sweet orange peel (Citrus sinensis) against Staphylococcus aureus ATCC 25923. Extraction was performed by maceration using 96% ethanol. Antibacterial activity was assessed by disc diffusion, MIC and MBC by dilution method, and combination effects by the paper strip method at ratios of 1:1, 1:2, and 2:1. Data were analyzed using One-Way ANOVA and Tukey's HSD test. Results showed that MIC and MBC of both single extracts were at 12.5%. Average inhibition zones of anting-anting leaves and sweet orange peel single extracts were 15.80 mm and 9.33 mm, respectively. The 1:1 combination produced the largest inhibition zone (18.57 mm). The paper strip method revealed a synergistic effect for the 1:1